2019
DOI: 10.1186/s12889-019-6885-z
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review of the impacts of urban agriculture on the determinants of health

Abstract: Background There has been an increasing interest in urban agriculture (UA) practice and research in recent years. Scholars have already reported numerous beneficial and potential adverse impacts of UA on health-related outcomes. This scoping review aims to explore these impacts and identify knowledge gaps for future UA studies. Methods A systematic search was conducted in seven electronic bibliographic databases to identify relevant peer-reviewed studies. Articles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 119 publications
4
59
0
2
Order By: Relevance
“…While we understand that arriving at a robust resilience assessment of the system would require mixed methods and longitudinal relationships (Berkes & Folke, 1998), the data presented here uses indicators to provide important insight into resilience that is both relevant for other Rust Belt urban agriculture initiatives and will facilitate the future development of participatory interventions in place to promote a more resilient urban agriculture system. We also build on the growing literature in urban agriculture motivations and barriers, which is primarily qualitative (Audate et al, 2019;Fox-Kämper et al, 2017;McVey et al, 2018;Pourias et al, 2016), by presenting a validated survey instrument for quantitative analysis of urban agriculture characteristics, and by integrating resilience indicators with motivations and barriers.…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation
“…While we understand that arriving at a robust resilience assessment of the system would require mixed methods and longitudinal relationships (Berkes & Folke, 1998), the data presented here uses indicators to provide important insight into resilience that is both relevant for other Rust Belt urban agriculture initiatives and will facilitate the future development of participatory interventions in place to promote a more resilient urban agriculture system. We also build on the growing literature in urban agriculture motivations and barriers, which is primarily qualitative (Audate et al, 2019;Fox-Kämper et al, 2017;McVey et al, 2018;Pourias et al, 2016), by presenting a validated survey instrument for quantitative analysis of urban agriculture characteristics, and by integrating resilience indicators with motivations and barriers.…”
Section: Core Ideasmentioning
confidence: 99%
“…Individuals' motivations for engaging in urban agriculture often include multiple benefits, rather than a single primary reason for participation (Kirkpatrick & Davison, 2018;Pourias, Aubry, & Duchemin, 2016). Many urban agriculture benefits are particularly important for women, immigrants, lowincome households, and minorities (Audate et al, 2019;Buckingham, 2005;Clarke & Jenerette, 2015;Graham & Connell, 2006). In addition to benefits to individuals and households, researchers have cataloged benefits of urban agriculture to the environment and communities.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, community garden evidence is predominantly qualitative looking at the perceived ecological, health, wellbeing and social implications of this setting whereas quantitative methods applied in the literature are inconsistent [9,40,41]. This paper describes a systematic review protocol to explore the range of indicators and impact measures currently used in the community garden literature.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on the measurement of community garden participation, this protocol recognises and builds on the work of Lovell et al [3], who previously published a search protocol focused on the health and wellbeing impacts of community gardening for adults and children. Further, recent studies like Genter et al [43], Ohly et al [44], Kunpeuk et al [45], and Audate et al [40] have reviewed such benefits identified in the literature associated with allotment gardening, gardening, and urban agriculture accordingly. The following protocol paper is unique compared to these studies in that it investigates how data has been collected to facilitate more consistent, robust and valid community gardening information being gathered in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has focused on the restorative, rehabilitative, and nutritional aspects of gardening activities for many different groups, such as convalescing patients [66], children with attention deficit disorder [47], homeless women [67], older people [68,69], and adults with clinical depression [70]. Furthermore, gardening has been shown to be beneficial in a variety of settings: allotments [71,72], other communal gardening settings [73][74][75][76], hospitals [66], nursing homes [77], and schools [78,79]. A recent report by the King's Fund demonstrates how gardening interventions play an important role in the UK's National Health Service and the wider health system [58].…”
Section: The Health Contextmentioning
confidence: 99%